2006
DOI: 10.1007/s00170-006-0539-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of techniques in the evaluation of springback and residual stress in hydroforming

Abstract: The increasing need for high strength complex hollow bodies for automotive application is pushing towards the use of sheet hydroforming techniques in conjunction with high strength steels. Unfortunately high strength steels are characterised by high springback levels. In this paper the springback and residual stresses have been analysed by means of laboratory trials carried out using the double sheet hydroforming technique. The attention has been focused on the upper blank of TRIP800 steel. The analysis has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The residual stresses can also be measured by carefully slicing (by electric discharge machining or laser cutting) a section of the component under study. The distortion of the section is a measure of locked in residual stresses [5]. However, all the destructive methods are limited to one measurement as the original stress distribution contained in the component is altered during destruction.…”
Section: Introductionmentioning
confidence: 99%
“…The residual stresses can also be measured by carefully slicing (by electric discharge machining or laser cutting) a section of the component under study. The distortion of the section is a measure of locked in residual stresses [5]. However, all the destructive methods are limited to one measurement as the original stress distribution contained in the component is altered during destruction.…”
Section: Introductionmentioning
confidence: 99%
“…The initial shape of this second mold corresponds to the final freeform shape and is iteratively modified to take into account the springback effect. 17 The FEA is performed in order to start a parametric analysis and to extract two relevant cases for the study using method one. The face-sheets are modeled with quadrangle elements that allow a fine meshing of the mirrors section.…”
Section: Modeling Methods and Study Casesmentioning
confidence: 99%
“…The evaluation of residual stress was performed using the x-ray diffraction. It was observed that high pressure allowed the obtaining of high equivalent plastic strain on the top region of the samples, with a subsequent reduction in springback [5] . The residual stress in the machined surface has three kinds of distribution: tensile stress, compressive stress and tensile-compressive stress.…”
Section: Introductionmentioning
confidence: 99%